A modified method for resected specimen processing in rectal cancer: Semi‐opened with transverse slicing for measuring of the circumferential resection margin. Issue 2 (7th November 2021) - Ishii, Masayuki; Takemasa, Ichiro; Okita, Kenji; Okuya, Koichi; Hamabe, Atsushi; Nishidate, Toshihiko; Akizuki, Emi; Sato, Yu; Miura, Ryo; Korai, Takahiro; Sugita, Shintaro; Hasegawa, Tadashi
Abstract: Circumferential resection margin (CRM) is essential for oncological quality assessment in rectal cancer surgery. CRM represents a surrogate parameter for oncological outcomes and is important for stratifying treatment strategies in Western nations. In Japan, the mesentery is removed for specimen processing in order to extract as many lymph nodes (LNs) as possible; consequently, CRM cannot be measured. Given the diversification of treatment strategies for rectal cancer, the lack of measurement of CRM to assess surgical outcomes is a crucial issue that must be resolved. Therefore, it is necessary to establish a method enabling measurement of CRM while enjoying the advantages of the Japanese method. In the method we developed, the mesentery is removed from the rectum more than 2 cm away from the tumor, and the vicinity of the tumor is circularized. It is necessary to investigate the usefulness of this method prospectively in a multi‐center study.